In Silico Characterization and Homology Modeling of a Cyanobacterial Phosphoenolpyruvate Carboxykinase Enzyme. (30th March 2013) - Smith, Aubrey A.; Caruso, Amanda
Abstract : ATP-dependent phosphoenolpyruvate carboxykinase (PEPCK) is a key catabolic enzyme found in various species of bacteria, plants, and yeast. PEPCK may play a role in carbon fixation in aquatic ecosystems consisting of photosynthetic cyanobacteria. RuBisCO-based CO2 fixation is prevalent in cyanobacteria through C3 intermediates; however, a significant amount of carbon flows into C4 acids during cyanobacterial photosynthesis. This indicates that a C4 mechanism for inorganic carbon fixation is prevalent in cyanobacteria with PEPCK as an important β -carboxylation enzyme. Newly available genomic information has confirmed the existence of putative PEPCK genes in a number of cyanobacterial species. This project represents the first structural and physicochemical study of cyanobacterial PEPCKs. Biocomputational analyses of cyanobacterial PEPCKs were performed and a homology model of Cyanothece sp. PCC 7424 PEPCK was generated. The modeled enzyme consists of an N-terminal and C-terminal domains with a mixed α / β topology with the active site located in a deep cleft between the two domains. Active site residues and those involved in metal ion coordination were found to be conserved in the cyanobacterial enzymes. An active site lid which is known to close upon substrate binding was also predicted. Amino acid stretches that are unique to cyanobacterial PEPCKs were also identified.